AI IS CHANGING ONLINE SHOPPING AND CUSTOMER EXPERIENCE - Sahu, Jagdish Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The manner that consumers shop online is changing due to artificial intelligence (AI). AI is speeding up, simplifying, and improving the user experience of online shopping with chatbots, personalized advertisements, and product recommendations. This study examines the advantages and disadvantages of AI, explains how it affects consumer experience, and looks at how e-commerce businesses are utilizing AI tools. Customers' reactions to AI in online buying are investigated using descriptive statistics and hypothesis testing. The findings indicate that AI improves consumer pleasure, fosters trust, and produces a more tailored experience.